-2yi=3y

Simple and best practice solution for -2yi=3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2yi=3y equation:


Simplifying
-2yi = 3y

Solving
-2iy = 3y

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '-2y'.
i = -1.5

Simplifying
i = -1.5

See similar equations:

| 2x-1/4=55 | | f(x)=x^2+7x+6 | | 10(x+3)=1x+51 | | 5.1(x-3.6)+4.5=3.1(3.5x-2.6) | | V=0.72*63.6*863 | | 6(3x-5)=6(5y+20) | | x^2+2x-7=13+x | | 1+c=12 | | -4x=-(2+2x) | | X^2+10x+24=x+6x-6 | | 2x-2y+1=0 | | 3(6n+3)=135 | | 64/200 | | a^3-a^2+a-5=0 | | x(x-3)+2=4 | | 142/x-320=251 | | 36*x/6-7=5 | | x/6*12-20=64 | | 11x+9=0 | | (3a+2)(2a-5)=0 | | -12=2t-38 | | -2.9m-5.9=-1.8m+9.7 | | 5y+4=-2(y+3) | | log(3)[5x+4]=log[5] | | (1-2a)(a+3)=0 | | 3(r+4)-(6+2r)=-11 | | 2,5x+10=20 | | 2,5+10=20 | | 3=5-m/4 | | 9+1=6n+9 | | 10,45-13,88= | | 3a+5=3-5a |

Equations solver categories